2009
DOI: 10.7202/038550ar
|View full text |Cite
|
Sign up to set email alerts
|

Les relations de travail tripartites et l’application des normes minimales du travail au Québec

Abstract: De nombreux travaux ont mis au jour l’inadéquation existant entre les lois du travail conçues pour des relations bipartites entre un salarié et un seul employeur clairement identifiable et les relations de travail tripartites qui découlent des nouveaux modes d’organisation de la production qu’adoptent les entreprises en quête de flexibilité. Le présent texte porte de manière particulière sur l’application d’une importante loi québécoise, la Loi sur les normes du travail, aux relations tripartites découlant du … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 2 publications
0
3
0
2
Order By: Relevance
“…Complaint-based systems continue to be the core foundation of employment standards enforcement in many jurisdictions across the Western world (Davidov, 2010; de Tonnancour and Vallée, 2009; Fine and Bartley, 2019; Vosko et al, 2019; Weil, 2018). Indeed, despite the increasing use of proactive measures to enforce employment standards in certain jurisdictions, including the focus of this study, Ontario, Canada, the bulk of employment standards enforcement remains reactive, compelled by violation claims submitted by workers themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Complaint-based systems continue to be the core foundation of employment standards enforcement in many jurisdictions across the Western world (Davidov, 2010; de Tonnancour and Vallée, 2009; Fine and Bartley, 2019; Vosko et al, 2019; Weil, 2018). Indeed, despite the increasing use of proactive measures to enforce employment standards in certain jurisdictions, including the focus of this study, Ontario, Canada, the bulk of employment standards enforcement remains reactive, compelled by violation claims submitted by workers themselves.…”
Section: Introductionmentioning
confidence: 99%
“…This transfer of risks towards external organizations and, ultimately, to the workers at the end of the line, has concrete consequences for the protection of the latter's labour rights, whether minimum labour standards (De Tonnancour and Vallée, 2009), health and safety rights (Lippel et al., 2004) or other types of labour rights.…”
Section: Multilateral Employment Relationships Legal Regulation Of Labour and Powermentioning
confidence: 99%
“…While employment standards have received some scholarly attention in Québec 45,46 and Ontario, 40,41 aside from the work of the committees previously mentioned, few studies have examined regulatory effectiveness of OSH legislation or WC legislation in these provinces with regard to TEA workers. Some studies examined precarious employment more generally and OSH/WC regulatory effectiveness, 42,[47][48][49] while there are case studies that have identified issues of concern from the perspective of regulatory effectiveness, noting that TEA workers were reticent to declare work injuries.…”
Section: Canadian Studiesmentioning
confidence: 99%